Mahar as Esteem, Not Price: Mediating Classical Fiqh, the Compilation of Islamic Law, and Custom in Indonesia's Plural Legal Order - Bayu Arif Mahendra; Aris Munandar; Zetty Nurzuliana (PFL: Plural Family Law Review, 2026)
Mahar (dowry) sits at the intersection of three normative orders in Indonesia, namely classical fiqh, state codification, and regional custom, yet it is increasingly misread as a price paid to acquire a wife. This distortion is sharpened by the social escalation and public display of expected amounts. The article asks how the Compilation of Islamic Law (Kompilasi Hukum Islam, KHI) mediates between classical jurisprudence and lived practice, and what that mediation reveals about the normative purpose of mahar. Prior scholarship has examined doctrine, codification, and social practice in isolation, leaving their interaction within Indonesia's plural legal order underexamined. Employing a doctrinal-normative method that reads the four Sunni schools alongside the KHI through the lenses of legal pluralism and maqāṣid al-sharīʿah, the study analyzes the legal foundation of mahar, its conditions of validity, its forms and amounts, and its codification in Indonesian positive law. The analysis shows that the schools converge in substance, affirming the wife's entitlement and the sufficiency of a modest gift, even where they diverge in technical classification, and that the KHI distills this shared principle of simplicity and mutual consent into an administrable rule while preserving the wife's protected right. It argues, within the sources examined, that mahar functions analytically as a marker of esteem and a vested entitlement of the wife rather than a transactional price. These findings carry direct implications for how the institution is taught in religious education and applied in the Religious Courts.